KEPATUHAN MASYARAKAT BERLALU LINTAS MELALUI PENGAWASAN E-TLE DI KOTA PALANGKA RAYA - Hanafiah, Novri (Causa: Jurnal Hukum dan Kewarganegaraan, 2024)
Technological advancements in the transportation sector have driven the development of more effective traffic monitoring systems, one of which is Electronic Traffic Law Enforcement (E-TLE). The city of Palangka Raya has implemented this system to enhance public compliance with traffic regulations. This study aims to analyze the impact of E-TLE implementation on road users' behavior and the factors influencing compliance levels. Research data were collected through interviews, surveys, and secondary data analysis from relevant agencies. The findings reveal that E-TLE monitoring can increase public awareness and compliance with traffic rules. However, challenges such as limited public outreach and inadequate supporting infrastructure still need to be addressed.